Evaluation of antioxidant activity in crude polysaccharide extracts from two date varieties (Tazerzait “Azerza” and Deglet-Nour) - Belhachemi, Mohammed Habib; Belmir, Sara; Mebarek, Mohammed Oulad; Reffis, Mohammed; Achour, Fatima Zahra (Future Science, 2024)
The fruit of the date palm, Phoenix dactylifera L. is extensively consumed in Arabian countries and is esteemed for its nutritional attributes, boasting high carbohydrate content and specific vitamins. This study aims to assess the antioxidant potential of polysaccharide extracts from the date palm fruit (Phoenix dactylifera L.) from two selected cultivars, Tazerzait “Azerza” and Deglet-Nour, originating from the Ghardaia region. Crude polysaccharides were extracted from the dates using distilled water followed by ethanol precipitation. Yields from this process were 3.14% for the Tazerzait cultivar and 4.75% for the Deglet-Nour cultivar, indicative of significant polysaccharide content, known for their diverse health benefits. Antioxidant activity was evaluated in vitro through DPPH and ABTS assays. Polysaccharide extracts exhibited noteworthy antioxidant activity, notably the Tazerzait variety. In the DPPH assay, the Tazerzait extract displayed an IC50 value of 4.66 mg/mL, indicating effective scavenging of free radicals. Moreover, in the ABTS assay, the extract demonstrated even more potent activity, with an IC50 value of 0.49 mg/mL, underscoring its robust antioxidant properties. These results underscore the strong antioxidant potential of Tazerzait polysaccharides. Polysaccharide extracts from the date palm fruit, particularly from the Tazerzait cultivar, exhibit significant antioxidant activity, highlighting their potential as natural antioxidants. This suggests avenues for their utilization in pharmaceutical and food industries to enhance human health.